Anodal and cathodal transcranial direct current stimulations of prefrontal cortex in a rodent model of Alzheimer’s disease - Duan, Mengsi; Meng, Zhiqiang; Yuan, Dong; Zhang, Yunfan; Tang, Tao; Chen, Zhuangfei; Fu, Yu (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a leading cause of dementia in the elderly, with no effective treatment currently available. Transcranial direct current stimulation (tDCS), a non-drug and non-invasive therapy, has been testified efficient in cognitive enhancement. This study aims to examine the effects of tDCS on brain function in a mouse model of AD. The amyloid precursor protein (APP) and presenilin 1 (PS1) transgenic mice (7-8 months old) were subjected to 20-min anodal and cathodal tDCS (atDCS and ctDCS; 300 μA, 3.12 mA / cm2) for continuous 5 days. tDCS was applied on the left frontal skull of the animals, targeting on their prefrontal cortex (PFC). Behavioral performances were assessed by open-field, Y-maze, Barnes maze and T-maze paradigms; and their PFC electroencephalogram (EEG) activities were recorded under spontaneous state and during Y-maze performance. Behaviorally, atDCS and ctDCS improved spatial learning and/or memory in AD mice without affecting their general locomotion and anxiety-like behaviors, but the effects depended on the testing paradigms. Interestingly, the memory improvements were accompanied by decreased PFC EEG delta (2-4 Hz) and increased EEG gamma (20-100 Hz) activities when the animals needed memory retrieval during task performance. The decreased EEG delta activities could also be observed in animals under spontaneous state. Specifically, atDCS increased PFC EEG activity in the alpha band (8-12 Hz) for spontaneous state, whereas ctDCS increased that in alpha-beta band (8-20 Hz) for task-related state. In addition, some EEG changes after ctDCS could be found in other cortical regions except PFC. These data indicate that tDCS can reverse the situation of slower brain activity in AD mice, which may further lead to cognitive improvement. Our work highlights the potential clinical use of tDCS to restore neural network activity and improve cognition in AD.